Data related to "The role of solvent temperature and gas pressure on CO2 mass transfer during biogas upgrading within porous and dense-skin hollow fibre membrane contactors" - Luqmani, Benjamin A.; McAdam, Ewan; Pidou, Marc (Cranfield University, 2023)
Source data for published works: 'The role of solvent temperature and gas pressure on CO2 mass transfer during biogas upgrading within porous and dense-skin hollow fibre membrane contactors'.
Keywords: assymetric'; 'carbon capture (CCS)'; 'water'; 'biomethane'; 'selectivity'; 'permeability'